Promoting ecological restoration in France: issues and solutions. Issue 1 (19th December 2017) - Buisson, Elise; Jaunatre, Renaud; Regnery, Baptiste; Lucas, Marthe; Alignan, Jean‐François; Heckenroth, Alma; Muller, Isabelle; Bernez, Ivan; Combroux, Isabelle; Moussard, Stéphanie; Glasser, Thibaut; Jund, Simon; et al.
Abstract : Ecological restoration has developed greatly over recent decades. Promoting harmonious relationships between scientists and practitioners, between restoration ecology and ecological restoration, is essential to improving restoration projects. These relationships are difficult to achieve at a global scale, although international action remains essential. Therefore, regional and national networks are attempting to take up the challenge. With several European countries planning to create their own network in the coming years, insights from current practice are helpful. Here, we (1) describe the context in which ecological restoration is developing in France and (2) present the French restoration network, Réseau d'Echanges et de Valorisation en Ecologie de la Restauration (REVER). Most public policies related to restoration in France are derived from European Union (EU) directives, such as those on water, ecological networks, biodiversity, and protected species and natural habitat. Restoration can also be undertaken through Environmental Impact Assessment (EIA) or subsequent to damage. Following the model of the International Society for Ecological Restoration, the French network for ecological restoration (REVER) aims at accompanying and promoting restoration by facilitating relationships between the various stakeholders: practitioners, scientists, site managers, etc. To encourage exchange of knowledge and experience, REVER manages a website, organizes workshops, and provides links with SER‐Europe and Society for Ecological Restoration International (SERI). This article provides information that will be of interest to other countries trying to meet the Aichi targets of the convention on biological diversity: the restoration of 15% of degraded ecosystems by 2020.